Relation of low back pain with lumbosacral transitional vertebrae in Eastern Indian population - Dona Saha; Asutosh Pramanik; Gopal Chandra Mondal; Suchismita Ghosh; Pal, Madhushree; Falguni Mondal (Asian Journal of Medical Sciences, 2024)
Background: Lumbosacral transitional vertebrae (LSTV) or lumbarization of sacral vertebrae and sacralization of lumbar vertebrae are congenital variations. These are associated with alterations in anatomy and biomechanics of spinal and paraspinal structures, which lead to low back pain (LBP). Aims and Objectives: This radiological study was designed to identify the prevalence of LSTV in patients presenting with LBP and to classify the anatomical variations in LSTV according to the Castellvi classification. Materials and Methods: This hospital-based, cross-sectional, observational cohort study was conducted in the Department of Radiodiagnosis, in different medical colleges and hospitals of West Bengal. The study was done on 1500 patients aged 20–75 years with a history of LBP. Antero-posterior and lateral lumbosacral radiographs were done to identify LSTV. Results: The present study in West Bengal shows that 24.1% of subjects had LSTV among LBP patients, Castellvi Type IIA (33.4%) being the most common anatomical variant, followed by Type IB (19.6%). Sacralization (22.3%) was found more common than lumbarization (1.8%). Conclusion: LSTV comprises almost one-fourth of cases of low back ache which can be easily diagnosed by simple radiograph. It has important implications for surgery in the lumbosacral region.